Diabetes mellitus associated with type A insulin resistance - E. A. Sechko; T. L. Kuraeva; V. A. Peterkova; D. N. Laptev (Сахарный диабет, 2023)
Insulin resistance type A is a monogenic disorder with insulin action defect, observed in females with acanthosis nigricans (AN), hyperandrogenism, hyperinsulinemia, insulin resistance (IR) without obesity. We present a family case of diabetes mellitus (DM) with IR in two sisters with obesity and positive family history of DM in three generations. Hyperglycemia was identified at the age of 13 in the older sister and at 11 in the younger sister after COVID-19. Type 2 diabetes (DM2) was diagnosed in mother in the same time with children. Maternal grandmother was diagnosed with DM2 in 58 years old. Patients were examined in 6 months after diagnosis hyperglycemia in Endocrinology Research Centre. The older sister had obesity, AN, and striae distensae. Glycosylated hemoglobin (HbA1c) 6.2%. Impaired glucose tolerance (IGT), hyperinsulinemia and IR, hyperandrogenism, non-alcoholic fatty liver disease (NAFLD), arterial hypertension were diagnosed. The younger sister had obesity, striae distensae. HbA1c — 6.0%. Impaired fasting glucose (IFG), IGT, hyperinsulinemia, IR, NAFLD were diagnosed. Antibodies (AAb) to ZnT8A, IA2, GAD absented in both sisters. A genetic test was provided, a heterozygous mutation in the INSR gene p.V167M was identified in both sisters, mother and grandmother. IR type A was identified in a family with the phenotype of DM2 in this case. This case demonstrated that children with carbohydrate metabolism disorders and obesity without Islet cell autoantibodies have to reffered for a genetic testing. Disordered carbohydrate metabolism was diagnosed in the same time after a COVID-19 in three family members who did not previously have disordered carbohydrate metabolism. We suppose that SARS-CoV-2 can be a trigger for the development of carbohydrate metabolism disorders in IR type A.